Blood-Borne Metabolic Factors in Obesity Exacerbate Injury-Induced Gliosis - Hsuchou, Hung (2012)
Reactive gliosis, a sign of neuroinflammation, has been observed in mice with adult-onset obesity as well as CNS injury. The hypothesis that obesity-derived metabolic factors exacerbate reactive gliosis in response to mechanical injury was tested here on cultured primary glial cells subjected to a well-established model of scratch wound injury. Cells treated with serum from mice with diet-induced obesity (DIO) showed higher immunoreactivity of CD11b (marker for microglia) and GFAP (marker for astrocytes), with morphological changes at both the injury border and areas away from the injury. The effect of DIO serum was greater than that of scratch injury alone. Leptin was almost as effective as DIO serum in inducing microgliosis and astrogliosis in a dose-response manner. By contrast, C-reactive protein (CRP) mainly induced microgliosis in noninjured cells; injury-induced factors appeared to attenuate this effect. The effect of CRP also differed from the effect of the antibiotic minocycline. Minocycline attenuated the microgliosis and to a lesser extent astrogliosis, particularly in CRP-treated cells, thus serving as a negative control. We conclude that blood-borne proinflammatory metabolic factors in obesity increase reactive gliosis and probably exacerbate CNS injury.